Psychological Impact on Stunting Adolescents: Literature Review Study - Delima, Delima; Neviyarni, Neviyarni; Marjohan, Marjohan; Ifdil, Ifdil; Afdal, Afdal (Universitas Fort De Kock Bukittinggi, 2023)
Background: The impact caused by stunting is not only on physical development but will also have an impact on the child's psychology. Adolescents with stunting need to have high spirits so that they can be able and survive in life they avoid psychological impacts such as stress, withdrawal, depression, anxiety, and fear. The purpose of this study was to see the psychological impact caused by stunting in adolescence. Methods: The literature review method was used to search for articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline. Results: The search was carried out using the keywords